Edukasi Perawatan Genetalia pada Wanita Usia Subur di Posyandu Pringsewu Barat - Cynthia Puspariny (PUAN INDONESIA, 2020)
Genetalia hyegiene or genitals personal hygiene is atreatment that includes the genital hygiene that you perform yourself. This activity provides genitalia care education that focuses on maintening the genital pH of women of childbearing potential to increase mothers motivation and ability to perform daily gene care at home. This Activity aims at the mother who come to Posyandu to weigh their babies in the west of Pringsewu Posyandu with a total of 42 partisipants. The learning method used is providing theories and exercise that show how to deal with genetals. Many participants were thrilled to ask questiona 90% of the participants had a better understanding of how to properly care for genes. Development of other methods that can help fully educate genetalia care and strengthen the role of the husband as a form of family support in maintening reproductive health so that the mathers motivation to care for genetalia can be increased.